2018
DOI: 10.1101/244780
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Phylogenomics and barcoding ofPanax: toward the identification of ginseng species

Abstract: 11Background 12The economic value of ginseng in the global medicinal plant trade is estimated to be in excess 13 of US$2.1 billion. At the same time, the evolutionary placement of ginseng (Panax ginseng) 14 and the complex evolutionary history of the genus is poorly understood despite several 15 molecular phylogenetic studies. In this study, we use a full plastome phylogenomic 16 framework to resolve relationships in Panax and to identify molecular markers for species 17 discrimination. 18 Results 19We used hi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 119 publications
(113 reference statements)
1
1
0
Order By: Relevance
“…Analyses of complete plastomes recovered four major clades within Panax . These clades were also identified by the current study using standard DNA barcodes ( rbcL , matK and trnH‐psbA ), by Shi et al () using four plastid DNA regions, by Zuo et al () combining three plastid sequences and a mitochondrial DNA region, and by Jiang et al (), Manzanilla et al () and Liu, Yang, Yang, Yang, and Ji () using complete plastomes. However, with longer sequence length and more variable characters, or a much larger taxon sample than has previously been available, our data give the highest resolution to the relationships among and within these clades.…”
Section: Discussionsupporting
confidence: 66%
“…Analyses of complete plastomes recovered four major clades within Panax . These clades were also identified by the current study using standard DNA barcodes ( rbcL , matK and trnH‐psbA ), by Shi et al () using four plastid DNA regions, by Zuo et al () combining three plastid sequences and a mitochondrial DNA region, and by Jiang et al (), Manzanilla et al () and Liu, Yang, Yang, Yang, and Ji () using complete plastomes. However, with longer sequence length and more variable characters, or a much larger taxon sample than has previously been available, our data give the highest resolution to the relationships among and within these clades.…”
Section: Discussionsupporting
confidence: 66%
“…The known chromosomes for species in the genus Panax are mostly basal counts of x = 12 (Yi et al, 2004). In addition, phylogenetic analysis with the reported chloroplast genomes showed that four Panax species were grouped in the same genus and that P. vietnamensis was more closely related to P. notoginseng than P. ginseng and P. quinquefolius (Manzanilla et al, 2018;Nguyen et al, 2017).…”
Section: The Chromosome Numbers Of Ngoc Linh Ginsengmentioning
confidence: 99%